Socio-Onomastic Analysis of The Self-Naming of Balinese University Students - Liani, Made Devi (STKIP Agama Hindu Singaraja, 2024)
The aims of this research are to identify the patterns of the self-naming of the students in Ganesha Education University and investigate the categories of self-naming of Generation Z students at ELE Ganesha University of Education. This research uses a qualitative approach using survey methods. The data in this research are a number of names of Generation Z ELE students at Ganesha University of Education. By using the conventional equivalent analysis method. Researchers found that in self-naming among generation Z students there is a complex interaction between tradition, modernity, language and identity in forming self-naming practices, highlighting the dynamic nature of Balinese cultural identity in a rapidly changing world.